Порівняння точності оцінювання тривалості операцій IT-проєкту міграції IC до хмари - Шутько, В. В. (ХНУРЕ, 2024)
This work aims to conduct a comparative analysis of the original PERT method and the developed modification in the context of assessing the duration of operations of the IT project of migration of the information system to the Google Cloud platform. The criterion of comparison is the accuracy of the preliminary estimation when performing a certain list of operations of a real IT project. The context of the operations under consideration is obviously not based on the most probable scenario to show what accuracy of the preliminary estimate is demonstrated by the original method and the developed modification.
Keywords: порівняння точності; оцінювання тривалості; інформаційна система; PERT; IT-проєкт; Google Cloud Platform